Labour outcomes in advanced maternal age - Pisal, Priya B.; Palve, Tushar; Bulchandani, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Advanced maternal age has been traditionally defined as age >35 years at delivery, although some authors have used the age limits 40and even 44 years. Regardless of what is the cutoff for advanced maternal age, pregnancies in women aged >35 years are considered at risk of both obstetric complications and interventions. Methods: Study design: retrospective study. The present study is a type of research article which was conducted in the department of obstetrics and gynaecology, Cama Hospital, Mumbai from October 2021 to January 2022, 50 postnatal mothers with age more than or equal to 35 were selected. Results: About 50 women participated in this study and most of them belonged between the age group of 30-35 years of age. Most of the women were multipara. Most of them had postpartum hemorrhage as the most common post-delivery complication. Conclusions: Early ANC registration, regular ANC visits and adequate intrapartum fetal surveillance is essential to prevent adverse maternal and perinatal outcomes in advanced maternal age.